POTENTIAL TABAH BAMBOO SHOOTS FLOUR (GIGANTOCHLOA NIGROCILIATA BUSE-KURZ) IN STIMULATE LACTIC ACID BACTERIA GROWTH - Dylla Hanggaeni Dyah Puspaningrum; Cornelius Sri Murdo Yuwono (International Journal of Applied Science and Sustainable Development (IJASSD), 2019)
One of the varieties local of bamboo shoots is tabah bamboo shoots (Gigantochloa nigrociliata BUSE-KURZ), usually has and having dietary fiber content and nutrients. The potential diatery fiber and oligosaccharide of tabah bamboo shoots flour patient stimulate the growth of bacteria lactic acid (LAB) wanted to know in this study. This research consisting analysis total dietary fiber content food in enzymatic, the components of oligosaccharide with High Performance Liquid Chromatography (HPLC), and testing LAB growth in a media flour bamboo shoots patient. The experimental design used was a single-factor randomized block design (RBD). Results showing total dietary fiber on the patient bamboo shoots flour contents 18,29% (db) at the apical, 20,92% (db) at the middle and 14,22% (db) at the basal. The amount of total dietary fiber content obtained showed that tabah bamboo shoots flour has potential as a source of dietary fiber. Components of oligosaccharide in the tabah bamboo shoots flour presented descriptive. The highest content of 4,55% raffinose (db), and 0,35% sucrose (db). The content of simple carbohydrates in the flour has a tabah bamboo shoots can be a prebiotic. The growth of L. acidophilus, L. brevis, L. casei rhamnosus highest at the apical and the middle 2,8 x 1010 – 5,8 x 1010CFU/ml. Bifidobacterium bifidum highest at the basal 3,6 x 1010- 3,7 x 1010 CFU/ml. This shows that dietary fiber on tabah bamboo shoots flour able to stimulate BAL growth.